THE NEED TO INVEST IN THE GREEN ECONOMY - Asamkhodjaeva Shoira (European Science Publishing, 2024)
The article examines the concept of green economy, its necessity, its importance in sustainable development, its main goals, as well as its advantages. The directions and results of investments in the green economy have been studied. At the end of the work, the main conclusions were formed.
Keywords: green economy, investment, economic growth, economic efficiency, natural resources, ecology, energy resources, profit, need.